Late Holocene coastal land-use, site formation and site survival: Insights from five middens at Cape Leveque and Lombadina, Dampier Peninsula, Kimberley, Australia. Issue 2 (3rd May 2020) - Litster, Mirani; Barham, Anthony; Meyer, Juliet; Maloney, Tim Ryan; Shipton, Ceri; Fallon, Stewart; Willan, Richard C.; O'Connor, Sue
Abstract: This paper introduces primary data on site contents, chronology and stratigraphy for four subsurface middens, which formed through the late Holocene on the Dampier Peninsula. Data from one surface midden collection are also presented. In this monsoonal coastal locality, variations in dune stability and sand flux are critical to archaeological site formation and preservation. Site specific factors determining sand sequestration into topsoils interact with geomorphological processes and past human discard to determine the stratigraphy and chronology of individual sites. Taphonomic modes during the Anthropocene have shifted, such that middens are rapidly transformed by wind when exposed in back-beach areas. Processes of sand sequestration present management issues at midden sites, and their chances of survival into the future. The cultural assemblages from the middens are also discussed, with reference to the rich ethnoarchaeology of Bardi land-use and subsistence.